Elucidating associations between technetium pyrophosphate scintigraphy, echocardiography and cardiac biomarkers in transthyretin cardiac amyloidosis - Bennett Di Giovanni; Dakota Gustafson; Priya Arivalagan; Mitchell B Adamson; Julie Vishram-Nielsen; Diego Delgado (Open Heart)
Background Transthyretin amyloidosis is an under-recognised systemic disease whereby misfolded transthyretin proteins form fibrils capable of depositing in various tissues and organs. Despite improvements to diagnostic modalities, the associations between imaging techniques and clinical laboratory metrics remain unclear.Methods A single-centre retrospective cohort study was performed including 183 patients aged 18 years or older diagnosed with transthyretin cardiac amyloidosis (ATTR-CA) in a tertiary care setting. Linear regression and multivariate proportional hazard models were used to examine the associations between established imaging modalities (ie, technetium-99m pyrophosphate (99mTc-PYP) scintigraphy and echocardiography) and cardiac biomarkers (ie, cardiac troponin I and B-type natriuretic peptide (BNP)). The study included patients who visited the Toronto General Hospital Peter Munk Cardiac Centre between October 2012 and December 2022.Results Of the 183 patients included, 143 (78.1%) were male, with a median age (IQR) of 73.0 (66.0–79.0) years. Primary analyses revealed significant associations between positive 99mTc-PYP grading and echocardiographic parameters, particularly increased left ventricular (LV) mass (β=111.21, p=0.009) and greater interventricular septal thickness at end-diastole (IVSd) (β=0.48, p=0.003) in patients with hereditary transthyretin amyloidosis (ATTRm). Additionally, positive 99mTc-PYP grades correlated significantly with cardiac biomarkers, including log-transformed BNP (logBNP; β=1.99, p=0.002) in patients with ATTRm and log-transformed Troponin (logTroponin; β=1.68, p=0.007) in patients with wild type ATTR (ATTRwt). Conversely, the heart-to-contralateral lung ratio, a quantitative index derived from 99mTc-PYP scintigraphy, did not show significant correlations with cardiac biomarkers (logBNP and logTroponin), but demonstrated significant associations with LV mass (β=134.52, p=0.001) and IVSd (β=0.46, p=0.002) in patients with ATTRm.Conclusions These data suggest strong associations exist between cardiac biomarkers, structural echocardiographic changes and 99mTc-PYP scintigraphy, emphasising the importance of a multipronged diagnostic approach stratified by genotype.